Kamari Bedo: Dilema Perempuan dalam Ketidakpastian Status Pernikahan - Yanasti, Silfia; Jendrius, Jendrius; Maihasni, Maihasni (TEMALI : Jurnal Pembangunan Sosial, 2021)
Kamari bedo is an expression in the Minangkabau language used to describe a difficult position. Whatever this woman chooses in living her life, it always does not benefit the woman, causing a dilemma for women in the unclear marital status. This article aims to examine the dilemma of women in the unclear marital status. This study also tries to see the structure that empowers women in a dilemma in the unclear marital status. This approach applies a gender approach with qualitative research methods—data obtained through interviews with Nagari Taram women. Through the analysis of women who have unclear marital status in Nagari Taram as one of the Minangkabau areas, the researcher found that kamari bedo women are empowered by structures: the obligation of the wife to her partner, limited social activities, the obligation to cover family problems, the obligation to protect children, and a negative view of widows. It is what makes the bedroom of a kamari woman experience a dilemma in the unclear marital status.